DEVELOPMENT OF SCHOOL PRINCIPAL PROFESSIONALISM, THE MAIN KEY TO QUALITY EDUCATION - Fatihah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This journal discusses the professional development of school principals as the main key to quality schools/education. This research explores strategies for developing principal competencies, their impact on school performance, and their contribution to improving the quality of education. Research methods involve literature analysis, case studies, and surveys. The results provide indepth insight into the important role of school principals in improving the quality of education and provide recommendations for developing their professionalism. This study has significant implications for improving the education system as a whole.